Factors associated with safe sex among public school students in Minas Gerais, Brazil Fatores associados a sexo seguro entre alunos de escolas públicas em Minas Gerais, Brasil - Francisco José Machado Viana; Anibal Faúndes; Maeve Brito de Mello; Maria Helena de Sousa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
A cross-sectional study was conducted to evaluate factors associated with safe sex among sexually active public school students in Minas Gerais State, Brazil. The study focused on correlations between the variables gender, age, schooling, current grade, ethnicity, religion, importance attributed to religion, mothers' education, prior exposure to any sex education, promotion of juvenile protagonism, and participation by health professionals in school activities and consistent condom use with casual or stable partners and with use of other modern contraceptive methods. Bivariate and multivariate logistic regression analyses were used. Male gender and participation by health professionals in school activities were positively associated with all indicators of safe sex, and maternal schooling of more than eight years was positively associated with consistent condom use with casual and stable partners. Secondary (versus elementary) schooling and age (older) were inversely associated with consistent condom use with casual and stable partners, respectively. Ascribing greater importance to religion and Evangelical religion were negatively associated with use of modern contraceptives in the last sexual intercourse. Foi realizado um estudo de corte transversal para avaliar fatores associados à prática de sexo seguro entre estudantes sexualmente ativos de escolas públicas de Minas Gerais, Brasil. Estudou-se a associação de sexo, idade, escolaridade, turno, cor da pele, religião e importância dada à religião, educação da mãe, exposição à educação sexual, promoção do protagonismo juvenil pela escola e participação de profissionais de saúde no ensino, com uso consistente de condom com parceiro casual ou fixo, e uso de anticoncepcionais modernos. Utilizou-se análise bivariada e regressão logística multivariada. Ser do sexo masculino e ter envolvimento de profissionais de saúde no ensino estiveram positivamente associados com todos os indicadores de sexo seguro, e uma mãe com mais de oito anos de escolaridade esteve positivamente associado com uso de condom com parceiro fixo ou casual. Ser aluno do Ensino Médio (versus Fundamental) e ser mais velho associaram-se negativamente com uso consistente de condom com parceiro casual e fixo, respectivamente. Dar grande importância à religião e ser evangélico estiveram negativamente associados ao uso de anticoncepcionais modernos na última relação sexual.